Aerospace series. Connector, electrical and optical, rectangular, modular, rectangular inserts, operating temperature 175 °C (or 125 °C) continuous. Plug, size 1, with ground block, without mounting holes, class B and F. Product standard Part 013, (31st December 2015) - British Standards Institution,
No abstract available